Frå kvalitetsreform til studiereform og utdanningsreform. Nemningar og nemningsendring knytt til kvalitetsreforma - Akselberg, Gunnstein (Nordiske Studier i Leksikografi, 2005)
The author studies tcnns and novcl usagc tcnns rclating to the cvolution and implcmcntation of the «kvalitetsreform» (i.e. the quality reform) of Norwegian univcrsitics and university collcgcs. The study is bascd on Stortingsmelding nr. 27 (2000-2001) and othcr officia! documcnts issucd by the Ministry of Education and the Faculty of Arts at the University of Bergen. Term usagc and tcrminological innovations in thcsc documcnts are studicd in a communicativc pcrspcctivc, focusing on the transition domain bctwccn common laguagc and more tcchnical languagc. The terms used rcflcct not only the idcology bchind the rcfonn, but also purcly tcchnical aspccts of its practical implcmcntation. The terms ticd to the idcology bchind the rcfonn oftcn have a strong polyscmic charactcr, whcrcas the tcchnical terms oftcn have a more prccisc, though contcxt sensitive, scmantic dcnotation. Because of thcir strong polyscmic contcnt, thcrc is a considcrablc controvcrsy on the proper usagc of thcsc terms, which are oftcn used for purcly rhctorical purposcs.